2021
DOI: 10.3390/jcm10173842
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of COVID-19 Hospitalisation in Patients with Systemic Lupus Erythematosus: A Nationwide Cohort Study from Denmark

Abstract: Background: Patients with systemic lupus erythematosus (SLE) have an increased risk of infections due to impaired immune functions, disease activity, and treatment. This study investigated the impact of having SLE on the incidence of hospitalisation with COVID-19 infection. Methods: This was a nationwide cohort study from Denmark between 1 March 2020 to 2 February 2021, based on the linkage of several nationwide registers. The adjusted incidence of COVID-19 hospitalisation was estimated for patients with SLE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
2
28
1
1
Order By: Relevance
“…We found a relatively low number of patients with SLE among the French population with COVID-19-AOF (196 of 113 371, 0.2%) between March and November 2020, whereas Cordtz et al 21 recently reported an increased risk of hospitalisation for SLE patients with COVID-19 in Denmark compared with the general population. It might be due to a lack of precision in coding SLE procedures; however, our results fit well with the prevalence of SLE in France, estimated at 5 for 10 000 22.…”
Section: Discussioncontrasting
confidence: 64%
“…We found a relatively low number of patients with SLE among the French population with COVID-19-AOF (196 of 113 371, 0.2%) between March and November 2020, whereas Cordtz et al 21 recently reported an increased risk of hospitalisation for SLE patients with COVID-19 in Denmark compared with the general population. It might be due to a lack of precision in coding SLE procedures; however, our results fit well with the prevalence of SLE in France, estimated at 5 for 10 000 22.…”
Section: Discussioncontrasting
confidence: 64%
“…4 Several case series or single-centre/country studies suggest that some individuals with SLE can have a severe disease course, but the small size of these studies has precluded a comprehensive analysis of risk factors for poor COVID-19 outcomes. [5][6][7][8][9][10] We used the C19-GRA registry to identify sociodemographic and clinical factors associated with more severe COVID-19 outcomes in individuals with SLE.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…OpenSAFELY, a large analysis of primary care records of >17 million adults linked to 10 926 COVID-19-related deaths reported that after adjustment for a wide variety of factors such as demographic characteristics and comorbidities, those with autoimmune disease (SLE, RA or psoriasis as a group) had a higher risk of mortality, but this study did not adjust for medication use, nor did it evaluate SLE as a discrete or separate disease 4. Several case series or single-centre/country studies suggest that some individuals with SLE can have a severe disease course, but the small size of these studies has precluded a comprehensive analysis of risk factors for poor COVID-19 outcomes 5–10…”
Section: Introductionmentioning
confidence: 96%
“…The risk for hospitalization was three-fold higher than the general population as per a nationwide study in Denmark [ 23 ]. There was an increased risk associated with race (odds ratio [OR] 7.78 for non-Whites versus Whites, 95% CI 1.13–53.58), presence of comorbidities (OR 4.66, 95% CI 1.02–21.20), and body mass index (BMI) (1.08 per increase in kg/m 2 , 95% CI 0.99–1.18) as per results from the New York University (NYU) Lupus Cohort [ 24 ].…”
Section: Features Of Covid-19 In Patients With Sle and Effects Of Drugsmentioning
confidence: 99%